From Design to Evaluation: Authentic HOTS Reading Literacy Instruments with Quizizz Paper Mode - Destiani; Profithasari, Nindy; Dwi Saputra, Daniel; Wulandari Utamining Tias, Ika; Azizah, Alif Luthvi (International Journal of Learning Reformation in Elementary Education, 2024)
This study aims to develop higher-order thinking skills (HOTS)--based authentic reading literacy instruments using paper mode in the Quizizz application at Metro Public Elementary School 9, Lampung. This study used the Research and Development (R&D) method with the ADDIE design including the stages of Analysis, Design, Development, Implementation, and Evaluation. The results showed that the instruments developed met the criteria of good validity and reliability. The content validity and the language of the instrument were evaluated by experts with the results showing conformity with HOTS indicators, while the instrument's reliability was measured using Cronbach's Alpha coefficient with a value of 0.77, indicating adequate consistency. The implementation of the instrument in the 5th grade of Metro Public Elementary School 9 showed that the majority of students were able to understand the text well, as well as increased students' interest and motivation to learn through the use of paper mode Quizizz. However, some students still had difficulty in understanding the implied meaning and providing critical interpretation of the text. Teachers gave positive support to the use of this instrument, which was considered effective and interactive in improving higher-order thinking skills in students. The findings suggest that the development of technology-based instruments such as Quizizz can be an innovative solution in reading literacy assessment, although further refinement is needed to increase the effectiveness in measuring all spectrums of students' HOTS abilities.